2015
DOI: 10.1007/s00227-015-2618-8
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying variation in δ 13C and δ 15N isotopes within and between feathers and individuals: Is one sample enough?

Abstract: Studies of avian migration increasingly use stable isotope analysis to provide vital trophic and spatial markers. However, when interpreting differences in stable isotope values of feathers, many studies are forced to make assumptions about the timing of moult. A fundamental question remains about the consistency of these values within and between feathers from the same individual. In this study, we examine variation in carbon and nitrogen isotopes by sub-sampling feathers collected from the wings of adults of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
1
18
1
Order By: Relevance
“…d 2 H values differ with distance from the coast (Hobson, Michener & Lajtha, 2007) and d 13 C and d 2 H with increased aridity (Rubenstein & Hobson, 2004;Neto, Newton & Gosler, 2006;Hobson, Møller & Wilgenburg, 2013) and anthropogenic change (Hobson, 2007;Hobson et al, 2013), resulting in possible isotope differences between the African grey parrots from the more forested and mesic central Africa and from the xeric and agriculturally transformed western and eastern regions (Mayaux, 2004; Hobson et al, 2013). Often illegally caught African grey parrots are subjected to stressful and nutrient-deficient conditions, resulting in variable isotope values, as observed in several captive and wild bird studies (Hobson & Clark, 1992b;Bearhop, Waldron & Votier, 2002;Fox, Hobson & Kahlert, 2009;Grecian, McGill & Phillips, 2012), where body stores are utilized to recover from nutrient deficient situations. The variability in d 13 C and d 2 H isotope values in the unknown and captive feathers was greater than the wild samples, and likely a result of differences in diet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…d 2 H values differ with distance from the coast (Hobson, Michener & Lajtha, 2007) and d 13 C and d 2 H with increased aridity (Rubenstein & Hobson, 2004;Neto, Newton & Gosler, 2006;Hobson, Møller & Wilgenburg, 2013) and anthropogenic change (Hobson, 2007;Hobson et al, 2013), resulting in possible isotope differences between the African grey parrots from the more forested and mesic central Africa and from the xeric and agriculturally transformed western and eastern regions (Mayaux, 2004; Hobson et al, 2013). Often illegally caught African grey parrots are subjected to stressful and nutrient-deficient conditions, resulting in variable isotope values, as observed in several captive and wild bird studies (Hobson & Clark, 1992b;Bearhop, Waldron & Votier, 2002;Fox, Hobson & Kahlert, 2009;Grecian, McGill & Phillips, 2012), where body stores are utilized to recover from nutrient deficient situations. The variability in d 13 C and d 2 H isotope values in the unknown and captive feathers was greater than the wild samples, and likely a result of differences in diet.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that primary feathers of bullfinches Pyrrhula pyrrhula and greenfinches Carduelis chloris grow slower than both body and tail feathers (Newton, 1967) and thus assimilate nutrients at different rates; this may also apply to African grey parrots. An alternative explanation could be the routing of d 13 C and d 15 N to different tissues or from different body pools for different tissues/feather types (Gannes et al, 1997;Bearhop et al, 2002;Ayliffe et al, 2004;Dalerum & Angerbjӧrn, 2005;Fox et al, 2009;Grecian et al, 2012;Storm-Suke, Norris & Wassenaar, 2012).…”
Section: Inter-feather Isotope Variationmentioning
confidence: 99%
“…Validation and standardization of the sampling of archival tissues to infer ecological and physiological traits, variation in diet or migration have been conducted in a number of species and for a variety of keratinous structures, such as human and other animal hair, pinniped vibrissae or bird feathers . These studies have involved assessment of variability within individuals and within repeated samples of the same individual.…”
Section: Discussionmentioning
confidence: 99%
“…Gardner et al (2015) reported two peak spawning periods for lionfish in the Cayman Islands occurring in spring and late summer, and spawning activity also peaks in summer in the eastern Gulf of Mexico (Fogg, Brown-Peterson & Peterson, 2013), North Carolina and The Bahamas (Morris Jr, 2009). Source populations for larvae settling in northeast Florida are not definitively known, but evidence from population genetics (Freshwater et al, 2009; Butterfield et al, 2015), biophysical modeling (Cowen, Paris & Srinivasan, 2006; Johnston & Purkis, 2011; Johnston & Purkis, 2015) and chronology of invasion history (Schofield, 2009) suggest a combination of self-recruitment and subsidies from upstream locations such as southern Florida and northern Cuba. Unfortunately, little is known about reproductive biology of lionfish in these regions.…”
Section: Discussionmentioning
confidence: 99%